LEGAL REGULATION OF BANKRUPTCY UNDER THE LEGISLATION OF THE REPUBLIC OF POLAND: COMPARATIVE AND LEGAL ASPECT - Khotsianovska, Natalia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose of the article is to study the legal regulation of bankruptcy under the legislation of the Republic of Poland in accordance with the current national legislation and its comparison with the legal regulation of bankruptcy in Ukraine. Research methods: the work uses the dialectical method of cognition, general scientific and special research methods. In particular, structural-functional, deductive methods and comparative-legal method. Results: the peculiarities of the legal regulation of the bankruptcy procedure according to the current legislation of the Republic of Poland are outlined. The specifics of the structure of its mechanism were considered and a comparison was made with the existing mechanism of legal regulation of bankruptcy in Ukraine and its role and significance at the current stage of the development of the economies of both states. The system of legal regulation is defined and attention is focused on the two-level legal regulation of bankruptcy in the Republic of Poland due to the participation of the Republic of Poland in the European Community. Acts of the supranational and national level in the field of legal regulation of bankruptcy, their interaction, significance and peculiarities at the current stage are analyzed. The main provisions and amendments of the supranational legislation on bankruptcy according to the acts of the European Community are defined. Distinctive features of the legal regulation of bankruptcy under the legislation of the Republic of Poland and the legislation of Ukraine, regarding its procedure and sources, are emphasized. The scope of the Law on Bankruptcy of the Republic of Poland is outlined. The most relevant research on the legal regulation of bankruptcy in the Republic of Poland from the point of view of legal practice is formulated. Discussion: study of the legal regulation of bankruptcy under the legislation of the Republic of Poland with the aim of unifying Ukrainian legislation to the requirements of the legislation of the European Community, taking into account positive and negative practice.